Al-Mūsīqīyah Fī NazamTuhfatul Qāshī Wa Dānī Fī Tarjamatī As-Syekh Muhammad Nawawi bin ‘Umar Al-Bantanī Lilzulfā Mustofā(Dirāsah ‘Arūdhīyah Wa Qawāfīyah) - Sari Yanti, Elva Dwi (Kitabina: Jurnal Bahasa dan Sastra Arab, 2025)
This research examines the nazam Tuhfatul Qāshī wa Dānī by Zulfa Musthofa in terms of ‘Arūdh and Qawāfī science. Nazam Tuhfatul Qāshī wa Dānī explains the life of Sheikh Nawawi Banten, the specialty of Nahdlatul Ulamā, and the challenges of Islamic propagation at that time which was hit by colonialism and the wahhābiyah movement. Arūdh and Qawāfī science are standardized classical rhythm rules if a nazam is not in accordance with these scientific rules, then the nazam is considered damaged. This type of research uses a descriptive qualitative method, where data collection is obtained from the text of the Tuhfatul Qāshī wa Dānī nazam. Then the data obtained is analyzed using the study of Arūdh and Qawāfī science. It can be concluded that this nazam uses bahr rajaz, zihāf, and illah. Zihāf is khaban, thayy and khabal. 'Illat is qatha'. Meanwhile, there are 3 forms of qāfīyah contained in the nazam, namely part of a word, one word and two words. In addition, there are also types of qāfīyah, namely: First, there are three names of qāfīyah, namely mutarākib, mutadārik and mutawātir. Second, there are 4 letters of qāfīyah, namely rawwī, washal, ta'sīs and khurūj. Third, there are 4 harakat qāfīyah, namely mujrā, nafādz, rass and taujīh. Fourth, there are 2 kinds of qāfīyah, namely qāfīyah mutlaqah and qāfīyah muqayyadah. And finally, there are no qāfīyah defects in the nadzam Tuhfatul Qāshī wa Dānī.